Kemampuan Pemahaman Dan Kemandirian Belajar Matematis Dengan Menggunakan Pendekatan Kontekstual - Dede Irmawati Oktora; Rippi Maya; Marchasan Lexbin Judah Riajanto (Journal on Education, 2019)
Mathematics is an important science possessed by every individual. One of the mathematical skills that must be possessed by students is the ability of understanding and independence of mathematical learning. This ability must be mastered by each student. But in fact, the level of students' mathematical understanding ability is still relatively low as well as with the independence of mathematical learning. So in this case required a solution in the learning of learning by using a contextual approach. The method used is quasi eksrimen with the sample selection is not random. The results of this study, indicate that the achievement and improvement of the ability of mathematical understanding using a contextual approach. Seen from the analysis of data obtained from both classes. However, to achieve the independence of mathematical learning is still not achieved well due to student conditions and time of execution that has not been maximized.